COVID-19 outbreak in Mauritania: epidemiology and health system response - Mohamed Lemine Cheikh Brahim Ahmed; Sidi Zehaf; Mohamed Mahmoud El Alem; Ahmed Elbara; Mohamed Mahmoud Ely Mahmoud; Mohamed Val Mohamed Abdellahi; Jorg Heukelbach (Journal of Infection in Developing Countries)
Introduction: In Africa, the first case of COVID-19 was reported in February 2020. Mauritania’s first case was confirmed in March 2020.